2016
DOI: 10.1007/s00128-016-1929-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Uranium and Thorium by Lemna minor and Lemna gibba in Pb-Zn-Ag Tailing Water

Abstract: This study focused on the ability of Lemna minor and Lemna gibba to remove U and Th in the tailing water of Keban, Turkey. These plants were placed in tailing water and individually fed to the reactors designed for these plants. Water and plant samples were collected daily from the mining area. The plants were ashed at 300°C for 1 day and analyzed by ICP-MS for U and Th. U was accumulated as a function of time by these plants, and performances between 110 % and 483 % for L. gibba, and between 218 % and 1194 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…e results of this study demonstrated that accumulation of Pb increased with the increase in concentration and duration of exposure. Results for accumulation of Pb are in line with the earlier studies on di erent aquatic plants like Wol a arrhiza, [49] Najas indica, [50] C. demersum, [51] Lemna minor, and Lemna gibba [52]. Uptake of iron by L. minor was increased gradually till the 12th day of experiment and exhibited a declining trend thereafter.…”
Section: Accumulation Of Heavy Metals Heavy Metal Accumulation In Drsupporting
confidence: 88%
“…e results of this study demonstrated that accumulation of Pb increased with the increase in concentration and duration of exposure. Results for accumulation of Pb are in line with the earlier studies on di erent aquatic plants like Wol a arrhiza, [49] Najas indica, [50] C. demersum, [51] Lemna minor, and Lemna gibba [52]. Uptake of iron by L. minor was increased gradually till the 12th day of experiment and exhibited a declining trend thereafter.…”
Section: Accumulation Of Heavy Metals Heavy Metal Accumulation In Drsupporting
confidence: 88%
“…Следовательно, избыток меди может вызвать окислительный стресс у растений, увеличение содержания высокотоксичных свободных радикалов, изменения в активности и содержании некоторых антиоксидантов (De Vos et al, 1992;. Высокий уровень окислительного стресса приводит к повреждению клеточных мембран, фотосинтетических пигментов, белков, нуклеиновых кислот и липидов, в конечном итоге к гибели клетки (Sasmaz, 2016). Окислительный стресс является причиной перекисного окисления липидов (ПОЛ), возникает целый каскад последовательных свободнорадикальных реакций с образованием различных химических соединений (спиртов, альдегидов, кетонов), обладающих высокой биологической активностью и токсичностью.…”
Section: Discussionunclassified
“…Metal uptake (MU), translocation/transfer factor (TF), bioconcentration factor (BCF), Percent metal uptake (% MU), Removal capacity (RC) and Toxicity index (TI). These models are repeatedly used in aquatic phytoremediation studies of metals in aqueous medium [48,156,177,175,176,141,155,44,143,165,158,146,137,166,167,168,171,172,148,139,150,173,210,211] and can also be used in organic pollutant remediation studies.…”
Section: Chemometrics For Aquatic Phytoremediationmentioning
confidence: 99%